Concept Modelling of Vehicle Joints and Beam-Like Structures through Dynamic FE-Based Methods - G. De Gaetano; D. Mundo; F. I. Cosco; C. Maletta; S. Donders (Shock and Vibration)
This paper presents dynamic methodologies able to obtain concept models of automotive beams and joints, which compare favourably with the existing literature methods, in terms of accuracy, easiness of implementation, and computational loads. For the concept beams, the proposed method is based on a dynamic finite element (FE) approach, which estimates the stiffness characteristics of equivalent 1D beam elements using the natural frequencies, computed by a modal analysis of the detailed 3D FE model of the structure. Concept beams are then connected to each other by a concept joint, which is obtained through a dynamic reduction technique that makes use of its vibration normal modes. The joint reduction is improved through the application of a new interface beam-to-joint element, able to interpolate accurately the nodal displacements of the outer contour of the section, to obtain displacements and rotations of the central connection node. The proposed approach is validated through an application case that is typical in vehicle body engineering: the analysis of a structure formed by three spot-welded thin-walled beams, connected by a joint.